EXPLORING THE LEXICAL COHESIONS USED IN SNOW WHITE AND THE HUNTSMAN MOVIE AND THE IMPLICATIONS TOWARD ELT - Karunia Eka Nafilatul Janah; Lilis Nur Hidayati (UPT Bahasa Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
This study aims to explore the lexical cohesions used in Snow White and the Huntsman movie as well as to reveal the implications toward English language teaching (ELT). This descriptive qualitative study focused on the lexical cohesions of synonyms, antonyms, and repetitions, the contexts and contributions of each element on plot establishment and the purpose of delivering the message. The findings showed that repetitions in the movie are mostly used than others; 67.7% repetitions, 25.8% synonyms, and 6.5% antonyms. The findings also showed that the lexical cohesions are presented under some contexts, emphasizing the utterance, making variations in the utterance, making contrast in the utterance, seeking agreement on something or making sure of something, and highlighting important points in the utterance. Furthermore, the findings also revealed that the lexical cohesions contribute to the plot establishment and the purpose of delivering the message of the movie because lexical cohesions are very useful in making the scenes in exposition, complication, crisis, climax, and resolution part of the movie more understandable and meaningful. Finally, the lexical cohesions can be potentially useful for ELT practices such as introducing and using lexical cohesions in teaching speaking and writing, finding spoken lexical cohesions in the teaching of listening, and examining lexical cohesions in texts through the teaching of reading because students have to be aware of the links that hold chunks of text together and that contribute to the creation of a text as a unit of meaning.